Нові дані про тваринництво ранньосередньовічного населення Верхнього Салтова - Колода, В.В.; Кройтор, Р.В.; Горбаненко, С.А. (Археологія, 2013)
На основі остеологічного матеріалу, виявленого під час досліджень у с. Верхній Салтів на рубежі ХХ —ХХI ст., проана- лізовано рівень і напрям розвитку ранньосередньовічного тваринництва на одній з найкраще досліджених (епонімній) пам’ятці салтівської культури (середина VIII — середина Х ст.). Проанализированы археозоологические материалы (раскопки 1996—1998 и 2004 гг. под руководством В.В. Коло- ды; определения Р.В. Кройтора) Верхнесалтовского археологического комплекса салтовской (салтово-маяцкой) культуры (середина VIII — середина Х вв.). Основной материал происходит из поселения; частично также при- влечены костные остатки из могильника.
Кости представлены только домашними животными: крупный рогатый скот (КРС) — 14 особей/26,9 %, мелкий рогатый скот (МРС) — 12 особей/23,1 %, свинья — 21 особь/40,4 %, конь — 5 особей/9,6 %. Обнаружены также ко- сти трех собак. В четырех катакомбах на могильнике 4 зафиксированы кости трех особей КРС и одной МРС.
Животных забивали в целом равномерно в течение года. Возрастное распределение забитых животных, сре- ди которых присутствуют ювинальные, полувзрослые и взрослые особи, убеждает в том, что сельское хозяйство было достаточно развито, а продукты земледелия, а также сенокосы позволяли содержать животных круглый год, не сокращая поголовье до минимума. Косвенным подтверждением хорошо развитых животноводства (сполна обеспечивавшего население мясными продуктами) и земледелия является отсутствие среди материалов костей диких животных.
Определенные различия показателей материалов из раскопок 1959—1961 и 1996—1998, 2004 гг. можно объ- яснить тем, что предыдущими исследованиями были охвачены городище и посад, последующими — только по- сад. Вполне вероятно, что на разных частях жилого памятника преобладали разные домашние животные и/или разные гастрономические предпочтения. Analyzed are archaeozoological materials (the excavations in 1996—1998 and 2004 under the guidance of V.V. Koloda, determinations by R.V. Croitor) from the Upper Saltiv archaeological site of Saltivska (Saltivska-Mayaky) culture (from the middle 8th c. to the middle 10th c.). Vast of the material comes from the settlement, and also bone remains from the burial ground are enlisted.
Bones are represented strictly by domestic animals: cattle – 14 individuals/26,9 %, small breed of cattle (SBC) – 12 individuals/ 23,1 %, pig – 21 individuals/40,4 %, horse – 5 individuals /9,6 %. Three dogs’ bones were also revealed. In four catacombs at the burial ground 4 the bones of three cattle and one SBC individuals were recorded.
Animals were in general rationally slaughtered during the year. Slaughtered animals’ age distribution included juvenile, semi-adult, and adult animals convince that the agriculture was quite developed and farming products, as well as haying allowed keeping animals for the whole year without reducing the livestock to the minimum. Lack of wild animals’ bones among the materials indirectly confirms the well developed cattle breeding (that completely provided the population with meat products) and agriculture.
Certain discrepancies in indexes of materials from the excavations in 1959—1961 and 1996—1998, 2004 can be explained by the fact that the hill-fort and «posad» (the citadel) were covered by the previous scholars and only «posad» was covered by the next ones. Probably at different parts of inhabited site certain domestic animals and/or certain gastronomic preferences prevailed.